The Development of Election Smart House Program as a Means of Political Education at KPUD Deli Serdang - Isnina Isnina; Dedi Amrizal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Election Smart House was established as a political education learning center for the community in increasing voter participation in the Deli Serdang KPUD. This study uses research and development methods, to find the best model in carrying out political education at the Deli Serdang KPU, especially in the THE Election Smart House Program. Collecting data on political education carried out by the Deli Serdang KPUD Election Smart House and then reviewing and planning the development of the Deli Serdang KPUD Election Smart House program as a means of political education. The results of the study found that Deli Serdang KPUD had been trying to provide as a facilitator to expand political information and education and the election agenda as well as increase voter participation. The implementation of the Deli Serdang KPUD Election Smart House program is carried out by utilizing space from one building or special building to carry out all public education programs or activities. For the development of the Deli Serdang KPUD The Election Smart House program using methods, namely (1) through face-to-face in Election Smart House by receiving visits (2) providing visits (3) social utilization (4) involving religious leaders, youth leaders and women leaders (eg OKP and Youth Organizations). ) and (5) urge political parties to be directly involved in conducting political education activities for the community youth leaders and women leaders (eg OKP and Youth Organizations).